Clinical characteristics and outcomes in 303 HIV-infected patients with invasive fungal infections: data from the Prospective Antifungal Therapy Alliance registry, a multicenter, observational study - Marukutira T (Dove Medical Press, 2014)
Tafireyi Marukutira,1 Shirish Huprikar,2 Nkechi Azie,3 Shun-Ping Quan,3 Herwig-Ulf Meier-Kriesche,3 David L Horn4 1Botswana-Baylor Children’s Clinical Centre of Excellence, Gaborone, Botswana, 2Icahn School of Medicine at Mount Sinai, New York, NY, 3Astellas Scientific and Medical Affairs, Inc, Northbrook, IL, 4David Horn LLC, Doylestown, PA, USA Abstract: This analysis aimed to characterize the epidemiology, diagnosis, treatment, and outcomes of invasive fungal infections (IFIs) in patients with human immunodeficiency virus (HIV). Data were examined for HIV patients enrolled in the Prospective Antifungal Therapy (PATH) Alliance registry, a multicenter, observational study of patients with IFIs in North America from 2004 to 2008. Patient demographics, clinical characteristics, comorbidities, antifungal therapies, and survival were assessed. In total, 320 fungal isolates were identified from 303 HIV patients with IFIs in the PATH Alliance® registry. These included Cryptococcus (50.0%), Candida (33.1%), Histoplasma (9.1%), and Aspergillus (4.4%). Candida infection occurred mainly as candidemia (86.0%); Cryptococcus as central nervous system infection (76.7%); Histoplasma as disseminated infection (74.1%); and Aspergillus as pulmonary infection (81.8%). The CD4 cell count was #200 cells/µL in 91.2% of patients with available data. The majority of patients with Cryptococcus (77.9%), Histoplasma (100.0%), and Aspergillus (71.4%) infections had CD4 cell counts ,50 cells/µL compared with 48.9% of patients with Candida infections. Patients with candidiasis were more likely to have other conditions requiring medical services compared with patients with other IFIs. Survival probability was lower in patients with Aspergillus (0.58) and Candida (0.59) infection than in patients with Histoplasma (0.84) and Cryptococcus (0.81) infection. In the highly active antiretroviral therapy era, traditional opportunistic IFIs such as cryptococcosis and histoplasmosis still mainly occur in HIV patients with CD4 counts ,50 cells/µL. Fungal infections remain a clinical challenge in HIV patients with severe immunosuppression. Our data also suggest that HIV patients with CD4 cell counts .200 cells/µL and other underlying conditions may be susceptible to invasive candidiasis. Keywords: human immunodeficiency virus, invasive fungal infections, Prospective Antifungal Therapy Alliance registry